2010
DOI: 10.19030/jabr.v26i1.275
|View full text |Cite
|
Sign up to set email alerts
|

A Cognitive Model Of Trust In E-Commerce: Evidence From A Field Study In China

Abstract: <p class="MsoNormal" style="text-align: justify; margin: 0in 0.5in 0pt;"><span style="font-size: 10pt; mso-bidi-font-style: italic;"><span style="font-family: Times New Roman;">Trust formation in the virtual environment is a complex process and is influenced by a plethora of factors.<span style="mso-spacerun: yes;">&nbsp; </span>This paper proposes a cognitive model of trust in e-commerce based on consumer research and the trust literature. It argues that perceived informative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 29 publications
(29 reference statements)
0
31
0
1
Order By: Relevance
“…Ability, benevolence, and integrity have been found to influence trust intention (Gill et al 2005), and propensity to trust has been found to predict trust in many studies (Chang and Fang 2013;Gao and Wu 2010;Jones, Leonard, and Riemenschneider 2009;Kim 2012;Kim and Prabhakar 2004;Teo and Liu 2007). Therefore, the current researchers propose: H1: The individual's disposition to trust will positively affect his=her trust of the web.…”
Section: Literature Review and Research Modelmentioning
confidence: 85%
See 1 more Smart Citation
“…Ability, benevolence, and integrity have been found to influence trust intention (Gill et al 2005), and propensity to trust has been found to predict trust in many studies (Chang and Fang 2013;Gao and Wu 2010;Jones, Leonard, and Riemenschneider 2009;Kim 2012;Kim and Prabhakar 2004;Teo and Liu 2007). Therefore, the current researchers propose: H1: The individual's disposition to trust will positively affect his=her trust of the web.…”
Section: Literature Review and Research Modelmentioning
confidence: 85%
“…Structural assurance and situational normality have been found to affect beliefs regarding institution-based trust (Wingreen and Baglione 2005). Trust has also been found to impact intended use in an online shopping environment (Aghdaie, Piraman, and Fathi 2011;Fang, Chiu, and Wang 2011;Gao and Wu 2010;Gefen et al 2003;Ha and Stoel 2009) and a social networking environment (Sledgianowski and Kulviwat 2009), to be key in understanding customer attitude and purchasing intention online (Ganguly et al 2010;Joia and De Oliveira 2008), and to be central in the intention to continually use the web (Vatanasombut et al 2008). These are all impacts on web use of the individual user.…”
Section: Web Trustmentioning
confidence: 99%
“…It became our second research question, namely; what are the categories, parameters, and indicators of trust presence that are both comprehensive and inclusive? This thinking is based on the collection of trust evaluation parameters from 10 literatures [5], [6], [7], [8], [9], [10], [11], [12], [13], and [14] in which each has a different viewpoint on trust.…”
Section: Faculty Of Computer Sciencementioning
confidence: 99%
“…This research's underlying viewpoint includes the development process of e-commerce sites [5], cognitive perspective [6], the C2C e-commerce [7], trust and distrust [8], functionality of the application [9], characteristics of trusted sites [10], trust blocks in E commerce [11], information within a merchant's website [12], trust enhancing factors [13], and trust forming mechanisms [14].…”
Section: E Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation